Photonuclear reactions by relativistic electron channeling radiation; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 465 - Bogdanov O. V. Oleg Viktorovich (2020, 2020)
Title screen